The brethren - Lewis, Beverly, 1949- (Minneapolis, Minn. : Bethany House, 2006)
Annie Zook, the Amish preacher's daughter, is caught between two world. LIving with shunned friend Esther, Annie longs to return to her forbidden art and the idyllic days spent with Englisher Ben Martin, before her father ordered her never to see him again.
Keywords: Children of clergy -- Fiction; Women artists -- Fiction; Amish -- Fiction; Christian fiction